1980
DOI: 10.5110/jjseg.21.80
|View full text |Cite
|
Sign up to set email alerts
|

Basement topography of the Kathmandu Valley, Nepal - An application of gravitational method to the survey of a tectonic basin in the Himalayas.

Abstract: Gravity survey was carried out to clarify the basement topography of the Kathmandu Valley which is filled with the Quaternary lacustrine sediments. A gravity anomaly map is produced from 112 gravity measurements within a major part of the Kathmandu Valley and a basement contour map is presented based on depth calculations along two sections. The maximum depth of the basement is estimated to be a little more than 650m from the present surface. Two distinct troughs of basement are detected in the central part of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 0 publications
0
36
0
Order By: Relevance
“…These features demonstrate that the long-period valley response of the Kathmandu Valley is considerably complicated, because they cannot be understood with one-dimensional seismic wave amplification. Previous studies indicated an uneven basement topography of the valley with many undulations (Moribayashi and Maruo 1980;Paudyal et al 2013) which may result in a complicated response. In order to understand the factors involved in the observed longperiod valley response of the Kathmandu Valley, we will have to clarify the three-dimensional underground structure of the valley in addition to the dense strong-motion observations in and around the valley.…”
Section: Ground Velocitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…These features demonstrate that the long-period valley response of the Kathmandu Valley is considerably complicated, because they cannot be understood with one-dimensional seismic wave amplification. Previous studies indicated an uneven basement topography of the valley with many undulations (Moribayashi and Maruo 1980;Paudyal et al 2013) which may result in a complicated response. In order to understand the factors involved in the observed longperiod valley response of the Kathmandu Valley, we will have to clarify the three-dimensional underground structure of the valley in addition to the dense strong-motion observations in and around the valley.…”
Section: Ground Velocitiesmentioning
confidence: 99%
“…Kathmandu, the capital city of Nepal, is located in the Kathmandu Valley. The valley is surrounded by mountains on all sides and is filled with soft lake sediments of Plio-Pleistocene origin (Dhital 2015); the thickness of the sediments is more than 650 m in the central part of the valley (Moribayashi and Maruo 1980). Large earthquakes in the past have caused significant damage in the Kathmandu Valley; for example, during the 1934 Nepal-Bihar earthquake (Mw 8.2), nearly 19 % of the buildings were destroyed inside the valley and more than 8000 people from all over the country lost their lives (Dixit et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…1a Figure 1a,b shows a simplified geological map and cross-section of the Kathmandu basin and location of the sampled section. The maximum thickness of the basin-fill sediments was estimated to be up to 650 m based on gravity data (Moribayashi and Maruo, 1980). The expected time span of sedimentation is mid-Pliocene to Pleistocene.…”
Section: Geological Setting and Samplingmentioning
confidence: 99%
“…This intermontane basin is filled with fluvio-lacustrine deposit ( Figure 1) whose depth is estimated to be more than 650 m at the central part (Moribayashi and Maruo 1980). In the Pleistocene, the uplift of mountain range south of Kathmandu was too rapid for the paleo-Bagmati River to drain its basin resulting in formation of a lake (Dhital 2015) which eventually drained 11-10,000 years ago (Sakai 2001) into the present form of the Kathmandu Valley.…”
Section: Length Termed As Main Central Thrust (Mct) Main Boundary Tmentioning
confidence: 99%